Design of a smart automated switching multi-channel, multi configurations resistivity meter - Fuad Abdulloh; Hartono Hartono; Farzand Abdullatif; Abdullah Nur Aziz (Universitas Jenderal Soedirman, 2026)
The resistivity method uses a resistivity meter to measure subsurface resistivity by measuring voltage and current. Conventional data acquisition involves manual electrode movement, which is time-consuming and error-prone. This research developed a multi-channel smart resistivity meter based on Internet of Things (IoT) technology with automatic electrode switching and automated measurements for Schlumberger, Wenner, and Dipole-dipole configurations. The automatic switching system uses relays controlled by an ESP32 master controller. The measurement system employs shunt resistor-based current sensors and voltage divider-based voltage sensors, integrated with Arduino Uno microcontrollers and ESP32 master. Data is automatically stored in cloud storage and controlled via mobile application. Testing results show 3% voltage and 2% current reading errors, with 92% voltage and 96% current precision within 0-100V and 0-100mA ranges. The system successfully performs automatic switching and uploads real-time data every 5 seconds, significantly improving geoelectrical data acquisition efficiency.